When the sheltered refuses adoption: from the analysis of the movie "Instant Family" (Research, Society and Development, 2021)
In the film is portrayed the reality of the adoption process, the existing prejudices, the difficulty of adopting a child/adolescent when he has an attachment to the family of origin and generally does not accept to be adopted by another family. The aim of this article was to analyze the influences of refusal in the adoption process by the child/adolescent, describing the adoption of children and adolescents that were living in orphanages in the movie "Instant Family". The methodology used the qualitative approach, with descriptive objectives, making use of textual analysis, content, image, and sound analysis. For the results, cognitive and behavioral bases were used to identify the important scenes of the film and discuss the themes presented with the authors. It was concluded that through an analysis of the speech and behavior of the characters, it was possible to realize that the older children take longer to feel confident and allow themselves to be part of a new family because the child believes he or she will not be loved in the unknown environment with people who still do not understand the child nor what motivated that person to adopt the child.